Benefits of the SHC System on Publication Management and Promotion of Sports Actor Services - Sapto Adi; Abi Fajar Fathoni (Physical Education and Sports: Studies and Research, 2022)
Background: Publication and promotion of the profession as a sports actor has not been seen optimally. One that shows this is that it is difficult to find traces of the legality of the profession, its achievements, and its relationships. Some of these traces are very important to know because they can be a measure of the quality of services so that the public can determine the appropriate sports players to meet the needs of services in the field of sports. For this reason, it is necessary to develop an online system that makes it easier for the public to obtain information related to sports actors. As well as helping sports actors for the publication and promotion of their profession. Objectives: The purpose of the research is to develop a Sport Human Connection (SHC) system that can help sports players for publication and promotion of their profession. Methods: This research method uses research and development methods. The research subjects were sports actors (coaches, athletes, management of sports institutions, masseurs, and physiotherapists) as many as 60 people. The selection of research subjects was done randomly. The data collection technique was carried out by conducting a survey. The research instrument used closed and open questionnaires. The data analysis technique used is descriptive quantitative data analysis and narrative analysis. Results: From the data obtained from the research subjects, it can be said that the SHC system has benefits for the publication and promotion of the profession of sports players with the support of features that display professional legality, achievements, relations, and communication features. Conclusion: Looking at the results of the study, it can be concluded that the SHC system provides the benefits of publication and promotion of the profession of sports players.